2021
DOI: 10.1038/s41419-021-03902-6
|View full text |Cite
|
Sign up to set email alerts
|

Puma, noxa, p53, and p63 differentially mediate stress pathway induced apoptosis

Abstract: Cellular stress can lead to several human disease pathologies due to aberrant cell death. The p53 family (tp53, tp63, and tp73) and downstream transcriptional apoptotic target genes (PUMA/BBC3 and NOXA/PMAIP1) have been implicated as mediators of stress signals. To evaluate the importance of key stress response components in vivo, we have generated zebrafish null alleles in puma, noxa, p53, p63, and p73. Utilizing these genetic mutants, we have deciphered that the apoptotic response to genotoxic stress require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 78 publications
0
26
0
Order By: Relevance
“…The cellular stress mediators, the p53 family, and their downstream transcriptional targets, such as PUMA and Noxa, play an important role during apoptosis. Cellular stress, including oxidative stress, DNA damage stress, and unfolded protein stress, typically lead to cell death and the clearance of stressed cells [ 66 ]. CHOP is involved in endoplasmic reticulum stress-induced apoptosis, in which the prolonged activation of unfolded endoplasmic reticulum proteins stimulates apoptotic cell death via the upregulation of CHOP [ 67 ].…”
Section: Efficacy and Mechanism Of Cbd On Cancermentioning
confidence: 99%
“…The cellular stress mediators, the p53 family, and their downstream transcriptional targets, such as PUMA and Noxa, play an important role during apoptosis. Cellular stress, including oxidative stress, DNA damage stress, and unfolded protein stress, typically lead to cell death and the clearance of stressed cells [ 66 ]. CHOP is involved in endoplasmic reticulum stress-induced apoptosis, in which the prolonged activation of unfolded endoplasmic reticulum proteins stimulates apoptotic cell death via the upregulation of CHOP [ 67 ].…”
Section: Efficacy and Mechanism Of Cbd On Cancermentioning
confidence: 99%
“…3 D). Additionally, it was reported that TP63 has been implicated as a mediator of stress signals, including ER stress and oxidative stress 18 . The expression of ΔNp63 was activated by ER stress in zebrafish 19 .…”
Section: Resultsmentioning
confidence: 99%
“…We then investigated the association of individual mRNAs with actively translating polysomes. To this extent, we first fractionated the cytoplasmic extracts of HeLa cells into four major fractions (1) mRNP fraction composed primarily of non-translated ribonucleoproteins; (2) monosome constituting mRNAs associated with a single ribosome; (3) light polysome that contains mRNAs associated with up to 3 ribosomes; and (4) heavy polysome that contains mRNAs with more than 3 ribosomes. We performed qPCR analyses with total RNAs phenol extracted from each fraction.…”
Section: Resultsmentioning
confidence: 99%
“…Although miCLIP-seq is a highly sensitive approach to examine m 6 A-methylated transcripts genomewide, the potential for false positive sites that might arise from a cross-hybridization mandates validation of m 6 A sites of interest (16). Thus, we employed SELECT (18) to confirm differential m 6 A methylation on four mRNAs, namely PHLDA1, PIDD1, PMAIP1 and TRAP1, all of which have been reported to be key players in modulation of apoptosis [Table 1; (4,(22)(23)(24)]. To this extent, we first used the m 6 A site at the 2525 th adenosine nucleotide of MALAT1 as a positive control to ensure that this method properly detects m 6 A-methylated residues (18).…”
Section: Cisplatin Modulates Major Changes In the M6a Rna Methylomementioning
confidence: 99%
See 1 more Smart Citation